Convergent chemoenzymatic synthesis of O-GalNAc rare cores 5, 7, 8 and their sialylated forms. Issue 7 (25th January 2023) - Gadi, Madhusudhan Reddy; Chen, Congcong; Bao, Shumin; Wang, Shuaishuai; Guo, Yuxi; Han, Jinghua; Xiao, Weidong; Li, Lei
Abstract : Mucin rare cores 5, 7, and 8 with 1, 2-cis glycosidic bonds were prepared with exclusive stereo-selectivity from a versatile precursor. Enzyme-catalyzed regio-selective sialylation was then achieved, yielding natural sialylated rare cores. Abstract : All O -GalNAc glycans are derived from 8 cores with 2 or 3 monosaccharides linked via α- or β-glycosidic bonds. While chemical and chemoenzymatic syntheses of β-linked cores 1–4 and 6 and derived glycans have been well developed, the preparation of α-linked rare cores 5, 7, and 8 is challenging due to the presence of this 1, 2-cis linkage. Meanwhile, the biosynthesis and functional roles of these structures are poorly understood. Herein, we synthesize 3 α-linked rare cores with exclusive α-configuration from a versatile precursor through multifaceted chemical modulations. Efficient regioselective α2-6sialylion of the rare cores was then achieved by Photobacterium damselae α2-6sialyltransferase-catalyzed reactions. These structures, together with β-linked cores 1–4 and 6, and their sialylated forms, were fabricated into a comprehensive O -GalNAc core microarray to profile the binding of clinically important GalNAc-specific lectins. It is found that only Tn, (sialyl-)core 5, and core 7 are the binders of WFL, VVL, and SBA, while DBA only recognized (sialyl-)core 5, and Jacalin is the only lectin that binds core 8. In addition, activity assays of human α- N -acetylgalactosaminide α2-6sialyltransferases (ST6GalNAcTs) towards the cores suggested that ST6GalNAc1 may be involved in the biosynthesis of previously identified sialyl-core 5 and sialyl-core 8 glycans. In conclusion, we provide efficient routes to access α-linked O -GalNAc rare cores and derived structures, which are valuable tools for functional glycomics studies of mucin O -glycans.